Cr2O3 nanoparticles anchored on ZnO nanorods as active heterostructure catalysts for phenol degradation - Lam, Sze-Mun; Sin, Jin-Chung; Abdul Rahman Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2018)
With the rapid civilization and industrialization, water pollution is becoming more and more intricate. Heterogeneous photocatalysis using metal oxide loaded ZnO nanorods is a well-known environmental technology to degrade toxic organic pollutants. In this study, Cr2O3 particles anchored on the ZnO nanorods (Cr2O3/ZnO) were successfully synthesized by a hydrothermal-deposition technique. Microscopic and crystallographic analyses indicated that the synthesized samples consisted of two-phase heterostructure of Cr2O3 and ZnO. The photocatalytic results showed that the phenol degradation by Cr2O3 /ZnO heterostructures was higher than those of pure ZnO and commercial TiO2. The synergetic effect between Cr2O3 and ZnO was the pivotal reason for the improvement of photoactivity as proven by the photoluminescence and terephthalic acid–photoluminescence analyses.